Analisa Pengaruh Variasi Sudut Sambungan Belokan Terhadap Head Losses Aliran Pipa - Zainudin, Zainudin; Adi Sayoga, I Made; Nuarsa, Made (Universitas Mataram, 2012)
On the water distribution, the connection of pipe bends is typically obtained either in industry or in housing. On the water distribution, it is often gained the lost of energy or head losses. The amount of head losses occurring in the connection of branch pipe is influenced by several factors, such as: diameter, flow, viscosity, and the angle at the bend pipe connections.This study aimed to determine the effect of variation of the connection point of the bend pipe to the head losses and pressure drop. To do it, the researcher uses an experimental method as a tool by varying the bend angle is 30o, 45o, 60o, and 90o. The result shows that head losses and the small pressure drop occur in the bend angle 30o is 73, 23 mm and 907.606 N/m2. While the head losses and pressure drop is the greatest at an angle of 90o, is 74, 80 mm and 1278,899 N/m2.